PEMAAFAN KORBAN DITINJAU DARI TUJUAN PEMIDANAAN DALAM PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Roby Anugrah (Jurnal Ilmu Hukum, 2019)
AbstractThe purpose of research is an effort to victim get proportional attention in determining criminal imposition of the perpetrators. So that a policy is needed in reforming the criminal law so that the position of the victim becomes more active in order to realize the purpose of punishment for the future (ius constituendum). In the Criminal Code the position of a passive victim is only a witness of a criminal case which is solely to prove the fault of the suspect or defendant. The research method used is the normative approach or a conceptual approach that is focused on examining the role of victims in the reform of criminal law in order to realize the purpose of punishment. The results of this study answer that in the Criminal Code the position of the victim is passive so that the purpose of punishment is only retributive without regard to the aspects of the victim. Furthermore, in the renewal of Indonesian criminal law, the victim will get a proportional place in determining the criminal imposition of the perpetrator with the principle of forgiveness by the victim in order to realize the objectives and guidelines for fair punishment. Keywords: Forgiveness of Victims, Reform of Criminal Law, Objective of Punishment.  AbstrakPenelitian ini bertujuan sebagai upaya agar korban mendapatkan perhatian yang proporsional dalam menentukan penjatuhan pidana terhadap pelaku. Sehingga diperlukan kebijakan dalam pembaharuan hukum pidana agar posisi korban menjadi lebih aktif guna mewujudkan tujuan pemidanaan untuk masa yang akan datang (ius constituendum). Dalam KUHP posisi korban pasif, hanya berkedudukan sebagai saksi dari suatu perkara pidana yang semata-mata untuk membuktikan kesalahan tersangka atau terdakwa. Metode penelitian yang digunakan pendekatan normatif atau conseptual  approach yang difokuskan untuk mengkaji peran korban dalam pembaharuan hukum pidana guna mewujudkan tujuan pemidanaan. Hasil penelitian ini menjawab bahwa dalam KUHP posisi korban pasif sehingga tujuan pemidanaan hanyalah bersifat pembalasan/retributive tanpa memperhatikan aspek korban. Selanjutnya pada pembaharuan hukum pidana Indonesia korban lebih mendapat tempat yang proporsional dalam menentukan penjatuhan pidana terhadap pelaku dengan adanya asas pemaafan oleh korban guna mewujudjan tujuan dan pedoman pemidanaan yang adil. Kata Kunci: Pemaafan Korban, Pembaharuan Hukum Pidana, Tujuan Pemidanaan